Potensi Daun Serai (Cympogon citratus) sebagai Sumber Karbon untuk Material Maju - Syilla Nurvidayah; Umar Kalmar Nizar (Departemen Kimia FMIPA UNP, 2023)
The purpose of this study was to determine the optimal carbonization temperature of lemongrass leaves to obtain an environmentally friendly, economical and quality product that could potentially be a carbon source for advanced materials. Lemongrass leaf carbon is synthesized by the carbonization process. The method in the formation of lemongrass leaf carbon is calcination using a furnace at a temperature variation of 250°C, 300°C and 350°C for 1 hour. Carbon will be tested for ash content, vapor content, and bound carbon content. Carbon quality requirements based on SNI 06-3730-1995. In conclusion, the optimal carbonization temperature is 250°C with an ash content of 18.99%, a vapor content of 2.91% and a bound carbon content of 78.10%.